1023 FEASIBILITY AND REPRODUCIBILITY OF LEFT ATRIAL STRAIN MEASURED WITH THE NEW DEDICATED SOFTWARE: A SPECKLE TRACKING STUDY. (15th December 2022) - Elena Mandoli, Giulia; Concetta Pastore, Maria; Pica, Andrea; Procopio, Cristina; Benfari, Giovanni; Cavigli, Luna; D´ascenzi, Flavio; Focardi, Marta; Valente, Serafin; Cameli, Matteo
Abstract: Background: During the last years, left atrial (LA) strain by speckle tracking echocardiography (STE) is gaining increasing evidence as diagnostic and prognostic tool in several clinical settings. However, the lack of a dedicated software was considered one of its main limitations, despite its proven good feasibility and reproducibility of a ventricular-based software. Importantly, brand-new fully automated software tools dedicated to the left atrium have been developed, both for on-line measurement on the echocardiographic machine and for off-line use on the workstation. Aims: to compare LA strain measures acquired by the new automated dedicated software with the "traditional" semi-automated ventricular based one, studying its feasibility, time-consumption, and reproducibility for the analysis of healthy, pressure-overloaded, and volume-overloaded patients. Methods: Grey scale apical 4-chamber view echocardiographic images acquired by an experienced operator (GE, Vivid E9, Orthern, Norway) in healthy patients, patients with pressure overload (arterial hypertension, aortic stenosis) and pressure-volume overload (mitral regurgitation, heart failure) were analyzed. STE was performed offline by two independent experienced operators, using both the semi-automated and the fully automated Echopac (Milwaukee, Wisconsin) software, which was then compared using matched-pairs analysis. Both operators were blinded to the other measures and repeated the same measurement on the same images after 10 days. Measurement of LA strain was performed on-line on the echocardiographic machine in a selected group of 20 patients by one of the two operators. Patients with prosthetic valves, heart transplantation, atrial fibrillation were excluded. Results: Overall, 100 patients were analyzed (41 healthy patients, 28 with pressure overload, 31 with pressure-volume overload). Peak atrial longitudinal strain (PALS) showed a high reproducibility with both methods. However, the dedicated method had a slightly higher inter-operator reproducibility (intraclass correlation coefficient(ICC)=0.97; 95% CI=[0.87;0.99] vs. ICC=0.96 [9.87;0.99]) (Fig.1 ) and intra-operator reproducibility (ICC=0.99 [0.99;0.99] vs. 0.98 [0.98;0.99] (Fig.2 ); correlation=0.85, p<0.001in operator 1 and 0.97 [0.95;0.98] vs. 0.95 [0.92;0.96]; correlation=0.83, p<0.001 in operator 2) with a slightly lower time consumption (90 s vs. 105 s) than the traditional ventricular-based one. On-line software showed a nearly perfect reproducibility with offline software [ICC=0.99 [0.99;1]] with a further time saving (60 vs. 90 s). Conclusions: the new fully automated software for the analysis of LA strain has a high inter-operator and intra-operator reproducibility. Both the automated and the traditionally used semi-automated software calculation provided optimal results in terms of reproducibility and time-consumption and could be equally chosen for strain calculation in daily clinical practice. LA strain calculation on-line on the echocardiographic machine proved to be reliable and time-saving. Fig. 1 Fig. 2